Akuntabilitas Pelayanan E-KTP Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Wajo - Syamsiar Syamsiar; Muh. Hasbi Abbas; Bakri Bakri; Zulfahri Zulfahri (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
This study aims to determine Service Accountability at the Wajo District Population and Civil Service Office using a quantitative research approach. Accountability is one of the factors in improving the quality of E-KTP services at the Wajo Regency Population and Civil Registration Office.The results of this study indicate that Accountability at the Wajo Regency Population and Civil Registration Office is in the very good category with an ideal score.